Nano-micro-mili Current to Mili Voltage Amplifier for Amperometric Electrical Biosensors. Issue 1 (February 2020) - Afnan Uda, M. N.; Parmin, N. A.; Jambek, Asral Bahari; Hashim, U.; Uda, M. N. A.; Shaharuddin, S. N. A.; Adam, Hussaini
Abstract: Amplification of nano and mircoampere electrical signal to the detectable range is essential in the biosensor field. This research is mainly focused on design an amplifier circuit to capture and amplify three different range of current as nano, micro and mili ampere and convert it to detectable voltage range as an output signal to the processing circuit. The Proteus 8 Pro software was used to design, simulate and calibrate the amplifier circuit. Firstly, current input as mili, micro and nano current were flown through 0.1 mΩ, 10 Ω and 10 KΩ resistors, respectively to convert different current inputs to the similar range in micro voltage. The MAX 4238 opamp IC was used to amplify micro voltage to mili voltage. LM 358 dual operational amplifier was used to supply virtual ground to MAX 4238 amplifier. The amplified output voltage of three different current inputs as nano, micro and mili were nearly equal to theoretical outputs.